Tumor volume regression during preoperative chemoradiotherapy for rectal cancer: a prospective observational study with weekly MRI. (3rd June 2018) - Van den Begin, Robbe; Kleijnen, Jean-Paul; Engels, Benedikt; Philippens, Marielle; van Asselen, Bram; Raaymakers, Bas; Reerink, Onne; De Ridder, Mark; Intven, Martijn
Abstract: Purpose: Few data is available on rectal tumor shrinkage during preoperative chemoradiotherapy (CRT). This regression pattern is interesting to optimize timing of dose escalation on the tumor. Methods: Gross tumor volumes (GTV) were contoured by two observers on magnetic resonance imaging (MRI) obtained before, weekly during, 2–4 weeks after, and 7–8 weeks after a 5-week course of concomitant CRT for rectal cancer. Results: Overall, 120 MRIs were acquired in 15 patients. A statistically significant tumor volume reduction is seen from the first week, and between any two time points ( p  < .007). At the end of CRT, 46.3% of the initial tumor volume remained, and 32.4% at time of surgery. PTV measured 61.2% at the end of treatment. Tumor shrinkage is the fastest in the beginning of treatment (26%/week), slows down to 7%/week in the last 2 weeks of CRT, and finally to 1.3%/week in the last 5 weeks before surgery. Conclusions: The main rectal tumor regression occurs during CRT course itself, and mostly in the first half, with shrinking speed decreasing over the course. This suggests that a sequential boost is preferably done after the elective fields, yielding an average PTV-reduction of 39%. A simultaneous integrated boost strategy could benefit from adaptive planning during the course.